Nuevo metodo para transporte de material vegetativo indexado de yuca (Manihot esculenta Crantz) - Lozano, J.C.; Laberry, R. (1988)
Cassava vegetative material is distributed by sending seedlings obtained from meristem cultures in test tubes. Although this material is accepted worldwide, losses occur due to seedling weakness and the delay to obtain adult seedlings in the field (normally between 3 and 4 yr). To overcome this problem, a system has been developed in which cuttings from indexed plants, obtained from meristem culture, are wrapped in waxed paper or paper towels, placing their tips on cotton saturated with a mixture of captan- benomyl (3000 ppm) at the end of the cuttings. They are then packed in groups in cardboard boxes for distribution. Dehydration is therefore avoided; cuttings also remain viable for over 15 days, enough time to be transported anywhere in the world. Bud germination and cutting rooting are achieved at 15 days and reach 100 percent. The seedlings obtained can be transplanted directly in the field just 1 mo. after their establishment. Adult plants can be obtained after a yr, which is highly advantageous considering previous losses and the time necessary to obtain adult plants in the field from seedlings in test tubes. (Full text-CIAT)